Annual cycle and inter-annual variation in the haul-out pattern of an increasing southern elephant seal colony - Lewis, Mirtha Noemi; Campagna, Claudio; Zavatti, Jorge (Antarctic Science)
The study describes the annual cycle of southern elephant seals for the increasing colony of Península Valdés, and compares it to the haul-out pattern reported for stable or decreasing sub-Antarcticcolonies of the species. Data were collected during censuses of the entire colony (nine breeding seasons, two moulting seasons and one autumn–winter haul-out), monthly surveys of coastline and mark-recapture of pups. Pup production during the study period grew from 12 113 to 14 621 animals (1995–2003). Most relevant events of the cycle were similar for all colonies studied, independent of the geographical location, size or population trend. Compared with other locations where southern elephant seals breed and moult, distinct features for Península Valdés were: i) breeding occurs earlier in the spring, and ii) most adult females reproduce and moult in the same colony. The increasing number of animals ashore was correlated with the expansion in pup production. Population trends and stability of demographic events could be related to a consistent physical environment (ocean fronts) during foraging phases of the annual cycle. Fil: Lewis, Mirtha Noemi. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Campagna, Claudio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Zavatti, Jorge. Universidad Nacional de la Patagonia. Facultad de Ciencias Naturales. Sede Puerto Madryn; Argentina